Effect of the Ethanolic Extract of Passiflora edulis F. Flavicarpa Leaves on Viability, Cytotoxicity and Apoptosis of Colon Cancer Cell Lines (2017)
ABSTRACT: Colorectal cancer is one of the main causes of morbidity and death in the world. This neoplasm is the second most frequent type of cancer and the fourth cause of cancer-related deaths worldwide; trends that may worsen in thecoming decades. This fact has motivated the search for alternatives to prevent this type of cancer, such as promoting the use of food phytochemicals capable of blocking, delaying or reversing the process of carcinogenesis, as many of these substances have been identified in fruits and have been classified as cancer initiation blockers or suppressors of tumor promotion/progression phases. In this study, phytochemicals from ethanolic leaf extracts of P.edulis F. Flavicarpa, were identified, and their biological activity on cell viability, cytotoxicity and pro-apoptotic potential were determined over SW480 and Caco-2 human cancer cell lines. Compounds with chemopreventive potential such as flavonoids, cardiotonic glycosides, alkaloids, among others, were found in the extract. The results show that these compounds have a dose-dependent effect on cell viability at concentrations higher than 5% (v/v%) and considerable proapoptotic potential due to an increase in activity levels of caspase 3. These results suggest a potential chemopreventive effect of the extract at an in vitro level on colon cancer cell lines.